Detection of tumour cells in the bloodstream of patients with uveal melanoma: influence of surgical manipulation on the dissemination of tumour cells in the bloodstream. Issue 4 (17th August 2015) - Charitoudis, Georgios; Schuster, Ronny; Joussen, Antonia M; Keilholz, Ulrich; Bechrakis, Nikolaos E
Abstract : Aim: The detection of circulating tumour cells in the bloodstream before and after surgical manipulation, and the qualitative detection of potential shedding of tumour cells during surgical manipulation of patients with uveal melanoma. Methods: 202 patients treated for a newly diagnosed uveal melanoma were included in the study. Blood samples were acquired 24 h before and 30 min after the basic surgical steps. Detection of potential circulating melanoma cells was extrapolated from the presence of tyrosinase and MelanA/Mart1 transcripts by reverse transcription PCR. Results: Based on the measurement of tyrosinase transcripts, as a result of the first and second surgical manipulation there were three and zero transitions from negative to positive respectively, while there were two and one transitions from positive to negative, respectively. According to MelanA/Mart1 transcripts, there were 19 and 5 transitions from negative to positive respectively, and 15 and 2 transitions from positive to negative, respectively. No statistically significant differences were documented, concerning the presence of circulating tumour cells in the blood samples acquired before and after the first surgical manipulation or the second one. Conclusion: The change in the percentage of patients with detected tumour cells in their bloodstream was not statistically significant. The frequent shifts from negative to positive samples as well as from positive to negative samples comparing preoperative to postoperative samples indicates discontinuous shedding or variation due to measurements close to the threshold of detection. As a conclusion, the surgical manipulation does not seem to have a measurable contribution to the spread of melanoma cells in the bloodstream.